Forward head posture affects the static and dynamic balance of bank workers - Gede Maheza Wiratama; Made Hendra Satria Nugraha; Ni Luh Nopi Andayani; Ni Komang Ayu Juni Antari (Physical Therapy Journal of Indonesia, 2024)
Background: Forward head posture (FHP) on bank workers who work a lot of time in front ofcomputer can cause balance problems due to anatomical changes in the neck. This can disrupt work productivity when further complaints occur. This research aimed to determine the relationship between FHP with static and dynamic balance among computer-using bank workers in Denpasar City. Methods: The study was an analytical observational study with a cross-sectional design. The sampling method used was purposive sampling. The sample size was 68 people determined by the Lemeshow method. Photogrammetry method used to assess CVA and determine FHP criteria. Single Leg Stance Test (SLS) was used to assess static balance, and the Star Excursion Balance Test (SEBT) was used to assess dynamic balance. The inclusion criteria were bank workers that had proven with an employee card, were 25-50 years of age, working with a computer for around 1-4 hours daily or more, had a minimum of one year of service as an employee, willing to be a subject, and filled out informed consent as the approval. Exclusion criteria included subjects having a history of musculoskeletal disorders. Results: Spearman rho analysis shows significant correlations between FHP with static and dynamic balance respectively, r = 0.817 and r =0.500 (p-values= 0.000). Conclusion: Based on the result, there are linear strong and moderate significance correlations between forward head posture with static and dynamic balance respectively on computer-using bank workers in Denpasar city. Posture education and stretching exercises through ergonomics training by the institution should be conducted to minimize the ongoing effects of FHP and prevent decreased work productivity.